Influence of resin molecular weight on curing and thermal degradation of plywood made from phenolic prepreg palm veneers - Ab. Wahab, Nor Hafizah; Md. Tahir, Paridah; Mohd Yunus, Nor Yuziah; Ashaari, Zaidon; Choo, Adrian Cheng Yong; Ibrahim, Nor Azowa (Taylor & Francis, 2014)
The present work evaluates curing and the thermal behavior of different molecular weight phenol formaldehyde (PF) resins used to prepare PF prepreg oil palm stem veneers. The physical properties (solid contents, gelation time, pH, and viscosity) of PF resins were determined. The molecular weight of resins was characterized by gel permeation chromatography, whilst thermal properties were determined by differential scanning calorimetry and thermogravimetric analyses. The average molecular weight of PF resins were 526 g/mole (low), 1889 g/mole (medium), and 5178 g/mole (control - commercial). Among the resins, medium (MMwPF) gives better thermal stability with a retained weight of 48.9% at 300°C. High (Commercial PF) had a low decomposition temperature (109.3°C) which occurred within 11 min. Both low (LMwPF) and MMwPF started to melt at ≥120°C. Based on strength and shear values, phenolic prepreg palm veneers can be prepared using either low or medium molecular weight PF but with varying results. In all cases, the mechanical properties of palm plywood made from PF prepreg veneers were superior to those made from PF-bonded plywood using the commercial process.